2013
DOI: 10.1111/cen.12316
|View full text |Cite
|
Sign up to set email alerts
|

An oral multiparticulate, modified‐release, hydrocortisone replacement therapy that provides physiological cortisol exposure

Abstract: Objective It is not possible with current hydrocortisone replacement to mimic the diurnal cortisol profile in patients with adrenal insufficiency. Previous attempts with modified release technology were unsuccessful. Our objective was to develop hydrocortisone formulations that recreate the diurnal cortisol profile using multi-particulate technology. Design and Measurements Screening by in-vitro dissolution profiles, pharmacokinetic testing in dexamethasone suppressed dogs and humans, and comparison to a ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(60 citation statements)
references
References 24 publications
1
58
0
1
Order By: Relevance
“…Plenadren® (ViroPharma SPRL, Brussels, Belgium) is currently available on the market for the treatment of AI, which provides a rapid increase in cortisol levels after intake in the morning followed by a gradual decrease over the day to almost undetectable levels in the night similar to the normal circadian rhythm [57]. Maybe even more promising for the treatment of AI in 21OHD is Chronocort®, which is currently being tested in clinical trials [52,58,59]. In 2 doses it might be able to provide an optimal cortisol profile to mimic the physiology of GC production and suppress adrenal androgens.…”
Section: Treatment Of Paimentioning
confidence: 99%
“…Plenadren® (ViroPharma SPRL, Brussels, Belgium) is currently available on the market for the treatment of AI, which provides a rapid increase in cortisol levels after intake in the morning followed by a gradual decrease over the day to almost undetectable levels in the night similar to the normal circadian rhythm [57]. Maybe even more promising for the treatment of AI in 21OHD is Chronocort®, which is currently being tested in clinical trials [52,58,59]. In 2 doses it might be able to provide an optimal cortisol profile to mimic the physiology of GC production and suppress adrenal androgens.…”
Section: Treatment Of Paimentioning
confidence: 99%
“…Chronocort was designed to release hydrocortisone in the last third of the small bowel to allow for delayed and sustained absorption (6). The multi-particulate formulation approach was selected to provide more predictable, reproducible gastrointestinal transit over single-unit oral dosage forms (14).…”
Section: Discussionmentioning
confidence: 99%
“…108 The cortisol time-exposure profile achieved using the once-daily dualrelease hydrocortisone treatment has been accompanied by an improvement in several clinical outcomes in patients with primary and secondary adrenal insufficiency. [108][109][110][111][112][113] Prospective trials have shown improved cardiovascular risk factors, glucose metabolism and quality of life in comparison with conventional treatment. 114 Interestingly, the daily doses of immediate release hydrocortisone and dual-release hydrocortisone was similar, suggesting that the pattern of hydrocortisone delivery and the circadian cortisol exposure-time profile may therefore be as crucial as the total daily dose in terms of patient outcomes.…”
Section: Timing/pat Tern Of Delivery Of G Luco Corti Coidsmentioning
confidence: 99%